Why do Kenyan children live on the streets? Evidence from a cross-section of semi-rural maternal caregivers. (January 2017) - Goodman, Michael L.; Martinez, Kelli; Keiser, Philip H.; Gitari, Stanley; Seidel, Sarah E.
Abstract: Globally, study of factors contributing to the street-migration of the tens of millions of street-involved children focus almost exclusively on children's perspectives. In this study, we assess household and maternal factors associated with street-migration of children through self-report of 1974 randomly selected women in semi-rural Kenya. Contributing new perspectives on this global phenomenon, data show a statistically significant association between increased maternal childhood adversities and street-migration of children (p < 0.001). Higher household wealth (p < 0.01) and maternal education (p < 0.05) were associated with lower odds of street-migration of children. Social support, reporting HIV+, school enrollment of biologically-related children, overall health, reported alcohol use, and functional literacy significantly mediated these pathways. Protecting children from street-migration in the next generation requires reducing childhood adversities in the present generation.